Peculiarities of international and national legislation and modern activity of leading companies in the extraction of colored gems - Shevchenko, Serhii; Husenko, Olha (Видавництво НТУ ДП, 2020)
Purpose. Study the impact of the peculiarities of international and national legislation in the field of colored gems mining on the success of the world's leading companies in order to activate the gemstone market in Ukraine. Methodology.Researches were performed by analyzing information from open sources, both scientific publications and annual reports of companies.
Keywords: colored gems; responsible mining; sustainable development; traceable supply chain